Plasma homocysteine, methionine and S-adenosylhomocysteine levels following high-dose methotrexate treatment in pediatric patients with acute lymphoblastic leukemia or Burkitt lymphoma: association with hepatotoxicity. Issue 7 (July 2014) - Kubota, Masaru; Nakata, Rieko; Adachi, Souichi; Watanabe, Ken-Ichiro; Heike, Toshio; Takeshita, Yasufumi; Shima, Midori
Abstract This study aimed to investigate: (i) changes of plasma homocysteine, methionine and S-adenosylhomocysteine levels following high-dose methotrexate (HD-MTX) treatment and (ii) the correlation of these sulfur-containing amino acids with MTX-induced hepatotoxicity. Fifteen pediatric patients with acute lymphoblastic leukemia and one patient with Burkitt lymphoma, with a total of 26 treatment courses of HD-MTX, were enrolled. Homocysteine levels increased at 24 h after HD-MTX treatment, and showed marginal decreases at 48 and 72 h. Methionine levels showed a biphasic pattern, i.e. an initial decrease at 24 h followed by increases at 48 and 72 h. S-adenosylhomocysteine exhibited a marginal decrease at 24 h. Changes of homocysteine exhibited significant correlation only with a maximum increase of alanine aminotransferase or total bilirubin from baseline. This study has demonstrated, for the first time, simultaneous changes of plasma homocysteine, methionine and S-adenosylhomocysteine following HD-MTX. The potential of homocysteine as a marker of hepatotoxicity is also presented.